Parallel regulation of constitutive NO synthase and renin at JGA of rat kidney under various stimuli - Bosse, Hans Martin; Böhm, Rita; Resch, Stefan; Bachmann, Sebastian (American journal of physiology, 1995)
Four chronic experiments were performed to assess changes in the activity and gene expression of type I nitric oxide synthase (NOS) at the macula densa (MD) and of renin expression and immunoreactivity (IR) at the juxtaglomerular apparatus (JGA) of rat kidney, as follows: 1) two-kidney, one-clip Goldblatt hypertension (2K1C, for 3 and 40 days; sham operation for controls), 2) furosemide treatment (150 mg/kg-1.day-1 ip for 5 days), 3) chronic low-salt diet (0.02%) vs. high-salt diet (3%; both for 11 days), and 4) chronic blockade of NOS by nitro-L-arginine methyl ester (L-NAME, 40 mg.kg-1.day-1 for 2 mo). NOS and renin gene expression, NOS enzyme activity and renin IR were semiquantitatively evaluated with histochemical methods (NADPH diaphorase, in situ hybridization, immunohistochemistry). In 2K1C, marked increases were induced in NOS and renin in the ischemic vs. contralateral kidneys both after 3 and 40 days, respectively (P < 0.05). Related to controls, significant increases in the ischemic kidney were encountered after 3 and 40 days, whereas contralateral suppression of NOS and renin was found only after 40 days. Furosemide treatment resulted in a marked increase of both NOS and renin levels compared with controls (P < 0.05). Salt restriction induced a significant elevation of NOS levels compared with salt loading (P < 0.05), whereas only minor changes were evident in renin levels. L-NAME treatment resulted in a moderate reduction of NOS activity (not significant), whereas renin levels were markedly reduced (P < 0.05). These results show that NOS activity and gene expression are inversely related to chronic changes in renal perfusion, salt balance, and salt transport at the distal tubule in parallel with the known response of renin to these changes. Inhibition of NOS decreases renin levels at the JGA. The histochemical findings support previous concepts that MD-derived NO is involved in the control of renin synthesis.
Gesehen am 23.11.2023